Q. 104.4( 63 Votes )

# Substituting <spa

Answer :

(A) On substituting x = -3 in the given expression, we get = (-3)2 + 5(-3) + 4 = 9 -15 + 4 = -2

Hence correct expression is: = (-3)2 + 5(-3) + 4 = 9 -15 + 4 = -2

(B) On substituting x = -3 in the given expression, we get = (-3)2 - 5(-3) + 4 = 9 +15 + 4 = 28

Hence correct expression is: = (-3)2 - 5(-3) + 4 = 9 +15 + 4 = 28

(C) On substituting x = -3 in the given expression, we get = (-3)2 + 5(-3) = 9 -15 = -6

Hence correct expression is: = (-3)2 + 5(-3) = 9 -15 = -6

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses RELATED QUESTIONS :

Solve: NCERT - Mathematics

Prove that:NCERT - Mathematics

Prove that:NCERT - Mathematics

Find the correct NCERT - Mathematics

Find the correct NCERT - Mathematics

Find the correct NCERT - Mathematics

Find the correct NCERT - Mathematics

Prove that:NCERT - Mathematics

Substituting <spaNCERT - Mathematics

Find the correct NCERT - Mathematics